Mapping and modeling of oil and gas relational data objects for warehouse development and efficient data mining - Nimmagadda, Shastri; Dreher, Heinz (IEEE Computer Society Press, 2006)
Oil and gas industries archive volumes of heterogeneous data. These companies, by virtue of their diverse operations, comprise of complicated organizational structure. The nature of organizational set-up with several operational units, often results with communication barriers among operational units. In order to effectively and efficiently perform oil and gas company's business activities, the flow of data and information must be consistent and sharing among its units. In order to improve information sharing among oil and gas company's personnel, heterogeneous data from various sources are integrated. Data warehouse is a solution, in which, oil and gas data entities, identified as class objects, are used for multidimensional modeling. Relational data structures constructed using these class objects, are stored in a warehousing environment to minimize the complexity of heterogeneous data and enhances power of data integration and information sharing among different operational units.